Airway Obstruction Due to Bronchial Vascular Injury after Sulfur Mustard Analog Inhalation - Veress, Livia A. (American Thoracic Society, 2010)
Rationale: Sulfur mustard (SM) is a frequently used chemical warfare agent, even in modern history. SM inhalation causes significant respiratory tract injury, with early complications due to airway obstructive bronchial casts, akin to those seen after smoke inhalation and in single-ventricle physiology. This process with SM is poorly understood because animal models are unavailable. Objectives: To develop a rat inhalation model for airway obstruction with the SM analog 2-chloroethyl ethyl sulfide (CEES), and to investigate the pathogenesis of bronchial cast formation. Methods: Adult rats were exposed to 0, 5, or 7.5% CEES in ethanol via nose-only aerosol inhalation (15 min). Airway microdissection and confocal microscopy were used to assess cast formation (4 and 18 h after exposure). Bronchoalveolar lavage fluid (BALF) retrieval and intravascular dye injection were done to evaluate vascular permeability. Measurements and Main Results: Bronchial casts, composed of abundant fibrin and lacking mucus, occluded dependent lobar bronchi within 18 hours of CEES exposure. BALF contained elevated concentrations of IgM, protein, and fibrin. Accumulation of fibrin-rich fluid in peribronchovascular regions (4 h) preceded cast formation. Monastral blue dye leakage identified bronchial vessels as the site of leakage. Conclusions: After CEES inhalation, increased permeability from damaged bronchial vessels underlying damaged airway epithelium leads to the appearance of plasma proteins in both peribronchovascular regions and BALF. The subsequent formation of fibrin-rich casts within the airways then leads to airways obstruction, causing significant morbidity and mortality acutely after exposure.